2018
DOI: 10.1111/cas.13538
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of leucine‐rich repeats and immunoglobulin‐like domains 1 by microRNA‐20a modulates gastric cancer multidrug resistance

Abstract: Multidrug resistance (MDR) significantly restricts the clinical efficacy of gastric cancer (GC) chemotherapy, and it is critical to search novel targets to predict and overcome MDR. Leucine‐rich repeats and immunoglobulin‐like domains 1 (LRIG1) has been proved to be correlated with drug resistance in several cancers. The present study revealed that LRIG1 was overexpressed in chemosensitive GC tissues and decreased expression of LRIG1 predicted poor survival in GC patients. We observed that upregulation of LRIG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Hence, identifying therapeutic targets is very helpful to GC treatment. Increasing evidence shows that miRNAs exert big effects on the occurrence, development, and drug resistance of GC . This study proved that miR‐876‐3p was downregulated in GC tissue samples in comparison with the corresponding normal tissues.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Hence, identifying therapeutic targets is very helpful to GC treatment. Increasing evidence shows that miRNAs exert big effects on the occurrence, development, and drug resistance of GC . This study proved that miR‐876‐3p was downregulated in GC tissue samples in comparison with the corresponding normal tissues.…”
Section: Discussionsupporting
confidence: 60%
“…Increasing evidence shows that miRNAs exert big effects on the occurrence, development, and drug resistance of GC. 9,10,24 This study proved that miR-876-3p was downregulated in GC tissue samples in comparison with the corresponding normal tissues. Additionally, miR-876-3p expression was inhibited in GC samples of cisplatinresistant patients compared with GC samples of cisplatin-sensitive patients.…”
Section: Discussionmentioning
confidence: 53%
“…7 Some experiments have shown that certain miRNAs, including miR-25, miR-20a, and miR-623 are associated with a poor prognosis of cancer and have been reported to be signicantly upregulated in recurrent gastric carcinoma. [8][9][10][11][12] Therefore, we hypothesized that gastric cancer resistance may be related to abnormal expression of miRNAs. In addition, a lot of evidence has revealed that miRNA is involved in gastric cancer initiation and progression, including MDR.…”
Section: Introductionmentioning
confidence: 99%
“…43 Loss of LRIG1 expression has been confirmed in human GC lesions, whereas EGFR expression is significantly increased, which indicates that LRIG1 down-regulation might accelerate carcinogenesis through EGFR activation. Recently, Zhou et al 44 reported that EGFR down-regulation through LRIG1 inhibition by miR-20a affected apoptosis in the GC cell line SGC7901 with respect to the mitogen-activated protein kinase/ERK and phosphoinositide 3-kinase/AKT pathways, affecting the multidrug-resistance process. A similar study reported that the regulation of LRIG1 expression by miR-19a affected glioma cell growth.…”
Section: Discussionmentioning
confidence: 99%